Design and Analysis of Ψ-Shaped UWB Antenna with Dual Band Notched Characteristics - Pandey G.K.; Singh H.S.; Bharti P.K.; Meshram M.K. (My University, 2025)
This manuscript presents, a compact dual band notched Ψ-shaped ultrawideband (UWB) monopole antenna. The antenna consists of a Ψ-shaped radiating patch loaded with the ω-shaped and inverted C-shaped slots. By properly optimizing the shape parameters of the ω-shaped slot and the inverted C-shaped slot along with the rectangular stub, dual band notched characteristics for Worldwide Interoperability for Microwave Access (3.3–3.8 GHz) and Wireless Local Area Network (5.15–5.825 GHz) is achieved, respectively. An equivalent RLC resonant circuit is proposed for the dual band notched characteristics of the antenna which is based on the current distribution and the input impedance characteristics of the antenna. The simulated and measured values of the VSWR and the input impedance characteristics are also compared with the values obtained from the equivalent circuit analysis. The simulated and measured results show that the proposed antenna has 2.5–11.5 GHz (about 129 % fractional bandwidth) operational impedance bandwidth (VSWR < 2) with dual band notched characteristics, stable radiation patterns, and good time domain characteristics which are essential for the UWB applications. © 2016, Springer Science+Business Media New York.